The idea of the university a reexamination - Pelikan, Jaroslav 1923-2006 (Yale Univ. Press, 1992)
The crisis in university education has been the subject of vigorous debate in recent years. In this eloquent and deeply personal book, a distinguished scholar reflects on the character and aims of the university, assessing its guiding principles, its practical functions, and its role in society. Jaroslav Pelikan provides a unique perspective on the university today by reexamining it in light of John Henry Cardinal Newman's 150-year-old classic The Idea of a University and showing how Cardinal Newman's ideas both illuminate and differ from current problems facing higher education. Pelikan begins by affirming the validity of Newman's first principle: that knowledge must be an end in itself. He goes on to make the case for the inseparability of research and teaching on both intellectual and practical grounds, stressing the virtues--free inquiry, scholarly honesty, civility in discourse, toleration of diverse beliefs and values, and trust in rationality and public verifiability--that must be practiced and taught by the university. He discusses the business of the university--the advancement of knowledge through research, the extension and interpretation of knowledge through undergraduate and graduate teaching, the preservation of knowledge in libraries, museums, and galleries, and the diffusion of knowledge through scholarly publishing. And he argues that by performing these tasks, by developing closer ties with other schools at all levels, and by involving the community in lifelong education, the university will make its greatest contribution to society.
Keywords: Newman, John Henry <1801-1890> / Idea of a university; Newman, John Henry <Cardinal, 1810-1890> / Idea of a university; Newman, John Henry <1801-1890> -- Idea of a university; Newman, John Henry -- Heiliger -- 1801-1890; Doelstellingen; Enseignement supérieur; Sociale verantwoordelijkheid; Universiteiten; Universités; Universität; Education, Higher; Universities and colleges; Höheres Bildungswesen; Theorie